Effect of initiators and ethoxylation degree of non-ionic emulsifiers on vinyl acetate and butyl acrylate emulsion copolymerization in the loop reactor - Sarac, A; Yidirim, H (JOHN WILEY & SONS INC, 2003)
Vinyl acetate and butyl acrylate copolymers were synthesized in the presence of ammonium persulfate and potassium persulfate initiators, mixture of non-ionic and anionic emulsifiers, and polyvinyl alcohol as protective colloid in a loop reactor. The monomer ratio was chosen 85:15. The series of non-ionic emulsifiers, which have 10-40 moles ethoxylated nonyl phenol, were combined with Nansa 66 (sodium dodecyl benzene sulfonate). The effects of the initiators on the physicochemical properties of copolymers were investigated by measuring conversion, viscosity, molecular weight, molecular weight distribution, and surface tension, respectively by using gravimetric method, Brookfield viscometer, gel permeation chromatograpy (GPC), and ring method. The effects of ethoxylation degrees of the non-ionic emulsifiers to the same properties of copolymers were also investigated. It was determined that the copolymer viscosities showed different tendency for two initiators. They were increased by the increasing ethoxylation degree of the non-ionic emulsifier for ammonium persulfate. In contrast, latex viscosity was decreased by increasing the ethoxylation degree in presence of potassium persulfate. Similar changes were also found in number average molecular weights of copolymers. On the other hand, weight average molecular weights of copolymers increased by increasing the ethoxylation degree of the non-ionic emulsifier for both initiators. In the case of potassium persulfate, the surface tension values of copolymers increased by increasing the ethoxylation degree, but generally increasing the ethoxylation degree did not affect the surface tension of copolymer very seriously for two initiators. (C) 2003 Wiley Periodicals, Inc.
Keywords: vinyl acetate; butyl acrylate; emulsion polymerization; degree of ethoxylation; MINIEMULSION COPOLYMERIZATION; LATEX FILMS; POLYMERIZATION PROCESS; METHYL-METHACRYLATE; CO-POLYMERIZATION; MORPHOLOGY; SURFACE; STATES; BATCH; Polymer Science